Study on Corneal Transplantation: Main Indications and Evaluation of Epidemiological Profile in a University Hospital - Bianca Prado Patrús; Augusto Terra Baccega; Gustavo Lustosa Neves; Flavia Santos; Larissa Batista Pegorin Ribeiro dos Santos; Marcelo Vicente de Andrade Sobrinho (Issues and Developments in Medicine and Medical Research Vol. 3, 2022)
Among transplants, the corneal is the most numerically expressive. This is due to the immunological privilege of the cornea which presents reduced rejection rates. In addition, capture, conservation and surgical techniques also contribute to this success. This chapter aims to evaluate about 60 medical records of patients undergoing corneal transplantation from January, 2015 to December, 2020.Keratoconus, leukoma, corneal dystrophy and post-facectomy decompensation are the main causes of optical transplants, having the latter a relationship with the number of preoperative cells and the skill of the surgeon. In hospitals where there are surgeons in training, there is an increase in corneal decompensation after facectomy. In terms of tectonic transplants in which the purpose is the preservation of the ocular structure, the main etiology is perforation due to trauma. From the observational and retrospective analysis of about 60 medical records of patients submitted to keratoplasty in the years 2015 to 2020, it is possible to understand the patients’ profile and main pathologies that evolve to transplantation in order to have an early diagnosis and to optimize their treatment.